Hydromineral Resources of Saline Lakes of Mongolia and Russian Altai; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Isupov V.; Vladimirov A.; Sodov A.; Kolpakova M. N. Marina Nikolaevna; Shvartsev S. L. Stepan Lvovich; Volkova N. (Chemistry and Physics of Materials, Environmental Materials, 2015)
Title screen